EdTech review: Teaching through Zoom – what we’ve learned as new online educators (Journal of Applied Learning and Teaching, 2020)
The Covid-19 mass migration to online teaching and learning has caused a seismic shift in the field of education. No longer is online learning education’s useful left arm – it was promoted to its beating heart overnight. As an Academic Learning Manager of a business school with over 3,000 students, I was tasked with providing Zoom training sessions for 200 lecturers a week before the start of a new trimester. Through more than 200 interactions with teachers over three months of training sessions, I observed us learning about ourselves as educators through the new zeitgeist of online delivery. This EdTech review briefly discusses Zoom and its features we’ve used for online teaching. However, it also explores three lessons that I believe we have learned from being new online teachers: the pitfalls of assumption, the need for adaptability, and the importance of empathy. Further research can explore whether those traditional on-campus teachers, who have been forced into online delivery, will continue to apply these three lessons to their following online teaching trimester.